Importance of organizational culture change in administrative implementation of current policies in the general accounting of the nation on modernization process of colombian state (2013)
The purpose of this research was to analyze the organizational culture in the development of the Colombian state in the implementation of Administrative Policies in the Accountant General of the Nation-State CGN Colombian, developing and verifying the implementation of the law on 152 1994 (Congreso de la Reublica de Colombia, 1994) which establishes the elements necessary for the preparation of the development plan, that in order to establish policies for organizational culture and management development policies in the CGN, facilitating compliance with institutional targets and allow the decision-making of the same for is useful to determine whether the implementation of policies and if necessary changing the organizational culture. The aim is to identify key considerations and their importance to perform a process of change in organizational culture of the Accountant General's Office as a requirement for the implementation of administrative policies of the development plan in 2013 as one of the activities necessary to meet the expectations of modernization of the Colombian state.